Green Policies at Home and Abroad (The Australasian Institute of Mining and Metallurgy, 1990)
Green policies have gained momentum since the 1972 Stockholm, Environment Conference. The environmental movement has influenced political initiatives both in New Zealand and abroad. Governments and international institutions have addressed local, regional and global environmental issues with varying degrees of success. New Zealand so far has not supported the United Nations' call for sustainable development in a consistent manner. New institutions and new rules for resource management mean there are opportunities to look after the land in different and more ecologically sensitive ways than has happened in the past. The increasing influence of regional councils in resource management planning will have important implications for mining and mineral exploration. These trends are discussed and possible future events outlined. Green policies have gained momentum since the 1972 Stockholm Environment Conference. Environmental issues are now global and the twentieth year Environment Conference planned for 1992 is likely to see new commitments made by world leaders and their national governments. Green politics may be the popular trend of the moment but green principles of managing the earth's resources are here to stay. There are many businessmen, many technologists, and many politicians who have hoped that the environmental movement was a passing fad and would fade into oblivion. The evidence is otherwise. Far from passing into oblivion, the environmental movement is growing rapidly. Each year brings further scientific data that indicates mankind is on a self destructive course unless we learn how to better manage the earth's natural resources. This information has contributed to a growing population of environmentally aware people. In the last 20 years there have been messages of concern about a population increase out of control and the energy crisis which focused on dwindling oil stocks. The issues are all interrelated including the present global issues of climate change and thinning ozone layers. The attention being given the messages by the United Nations and member states requires similar attention by industry. The problems have been identified; the challenge is to determine what should be done about them. Every challenge brings new opportunities and the future need not be doom and destruction. Mining is seen by some of the environmental action groups as unnecessarily destructive of the environment, but I do not see mining ceasing in the next few decades. Rather, the rules will be clearer with some areas excluded from mining, the methods of extraction will improve, the technology of processing will become more sophisticated and restoration of mining sites will be not only normal practice worldwide, but the end result may leave no hazards, may enhance the landscape and may result in acceptance of the industry by the general public. For that to happen, commitment and cooperation is required between the industry, the government, and society. As an Officer of Parliament my role is to review the system of agencies and processes established by Government for allocating, using and preserving natural resources and to report whether the system is maintaining and improving the quality of the environment. I also have a responsibility to see that the environmental planning and management carried out by public authorities is effective. That Ineans I have a keen interest in how the mining industry is administered by New Zealand public authorities, including Ministers of the Crown and district and regional councils. Today I intend to review the approach to resource management being taken by international agencies and by the New Zealand Government, and to comment on how environmental impact assessment for mineral exploration, as well as mining, may be administered in the future.